OSTEOMETRIC MORPHOMETRY OF PROXIMAL TIBIAL END IN INDIAN POPULATION: A FORENSIC POINT OF VIEW WITH ITS CLINICAL IMPORTANCE - GUSHINGE, MOHAN; GOVINDWAR, SONAL; PATEL, TEJAS (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Considering the importance of sexual dimorphism to the identification of skeletons for scientific, medical and forensic purposes, the aim of the present study was to investigate the gender of the person based on morphometric aspects of the proximal end of tibia in Indian population. Material and Method: This prospective descriptive study was carried out on 385 dry, adult tibias, which were collected from the department of Anatomy department of a medical college in north India. 385 fully ossified and processed dry bones were used to study. Unossified, injured or anomalous tibia bones were excluded from the study. Proximal end of tibia is studied under various parameters. After obtaining the values of the all parameters, data is corelated with the record section of the bone bank of the particular medical college. Result: It shows that, there is significant difference between male and female parameters and all results were statistically significant. Conclusion: This study will help to provide a basis for application in forensic science, in prosthesis, and in clinical practice also.